Clonality and the Phenotype–Genotype Correlation of Antimicrobial Resistance in Acinetobacter baumannii Isolates: A Multicenter Study of Clinical Isolates from Romania - Adrian-Gabriel Pană; Pavel Șchiopu; Dan Alexandru Țoc; Vlad Sever Neculicioiu; Anca Butiuc-Keul; Anca Farkas; Matei-Ștefan Dobrescu; Mirela Flonta; Carmen Costache; Izabella Éva Szász; Lia-Monica Junie (Microorganisms)
Antibiotic resistance is on the WHO’s top 10 list of global public health threats due to its rapid emergence and spread but also because of the high morbidity and mortality associated with it. Amongst the main species driving this phenomenon is A. baumannii, a member of the ESKAPE group of medical assistance-associated infections causing species famous for its extensively drug-resistant phenotypes. Our findings note a 91.52% frequency of extensively drug-resistant carbapenem-resistant A. baumannii (XDR CRAB) phenotype amongst clinical isolates from multiple hospitals in two major cities from northwestern and central Romania, harboring multiple antibiotic resistance genes such as blaOXA-23-like in 108 (91.5%) isolates, blaOXA-24/40-like in 88 (74.6%) isolates, blaNDM in 29 (25%) isolates, ArmA in 75 (63.6%) isolates, and ant(3″)-I in 69 (58.5%) isolates and sul1 in 113 (95.76%) isolates. The isolates, although nearly identical in phenotype, displayed different genotypical profiles, with varying degrees of similarity across hospitals and cities, raising the possibility of both local outbreaks of a single clone and widespread dissemination of resistant isolates.